2020
DOI: 10.7202/1073109ar
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Forestry in the FSC System: A Review

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To triangulate Measuring Organizational Performance in search of organizational excellence, the quality meta-assessment refers to the set of assessments to guide institutions towards best quality improvement practices (Ory, 1992). Likewise, it grants the venture the so-called reputational capital, which is primarily responsible for promoting the company's image to consumers, directly reflecting the organizational performance of the corporation, due to the sustainable model that the brand represents and takes to the market (Basso et al, 2020;Bulkan, 2020;Miles & Covin, 2000).…”
Section: Quality Meta-assessmentmentioning
confidence: 99%
“…To triangulate Measuring Organizational Performance in search of organizational excellence, the quality meta-assessment refers to the set of assessments to guide institutions towards best quality improvement practices (Ory, 1992). Likewise, it grants the venture the so-called reputational capital, which is primarily responsible for promoting the company's image to consumers, directly reflecting the organizational performance of the corporation, due to the sustainable model that the brand represents and takes to the market (Basso et al, 2020;Bulkan, 2020;Miles & Covin, 2000).…”
Section: Quality Meta-assessmentmentioning
confidence: 99%
“…Therefore, markets in the West are often seen as the primary consumer markets for eco‐certifications, with producers from both the developing world and the west supplying them (Naylor, 2014). While eco‐labels began on a national or regional scale to promote social and environmental change, they rapidly grew and opened offices to represent the scheme in various countries across the globe or created alliances with other eco‐certification (Bulkan, 2020; Herman, 2020; Nguyen & Dekhili, 2019). Using strategies such as advertisements, educational programs, articles in popular media, and events such as film screenings, eco‐certifiers achieved high levels of label recognition in many western countries (Dimitri & Oberholtzer, 2009; Peattie & Samuel, 2018; Perz et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on eco‐certification in developing countries has mainly focused on trade relationships between developing and developed economies (i.e., Bulkan, 2020; Lyon, 2007; Naylor, 2014). However, developing countries, like China and India, account for a rapidly growing proportion of global imports (Gereffi, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The progress of smallholder tree plantations have been recognized in other studies as requiring considerable tailored assistance schemes and capacity building on even use of their resources [1,7,[22][23][24]. Studies have shown an urgent need for disaggregated data on the different types of smallholder schemes to enable analysis of their benefits and costs against stated aspirations for smallholders [2,23]. In terms of nursery practice growing media is of major concern as this is where most variation in seedling performance occurs [25,26].…”
Section: Introductionmentioning
confidence: 99%